Biofeedback for Everyday Stress Management: A Systematic Review - Yu, Bin; Funk, Mathias; Hu, Jun; Wang, Qi; Feijs, Loe (Frontiers in ICT, 2018)
Background Mainly due to an increase in stress-related health problems and driven by recent technological advances in biosensors, microelectronics, computing platform, and human-computer interaction, ubiquitous physiological information will potentially transform the role of biofeedback in clinical treatment. Such technology is also likely to provide a useful tool for stress management in everyday life. The aim of this systematic review is to: 1) Classify biofeedback systems for stress management, with a special focus on biosensing techniques, bio-data computing approaches, biofeedback protocol, and feedback modality. 2) Review ways of evaluating approaches to biofeedback applications in terms of their effectiveness in stress management. Method A systematic literature search was conducted using keywords for “Biofeedback” and “Stress” within the following databases: PubMed, IEEE Xplore, ACM, and Scopus. Two independent reviewers were involved in selecting articles. Results We identified 103 studies published between 1990 and 2016, 46 of which met our inclusion criteria and were further analyzed. Based on the evidence reviewed, HRV, multimodal biofeedback, RSP, HR, and GSR appear to be the most common techniques for alleviating stress. Traditional screen-based visual displays remain the most common devices used for biofeedback display. Biofeedback applications are usually assessed by making both physiological and psychological measurements. Conclusions This review reveals several challenges related to biofeedback for everyday stress management, such as the facilitating user’s perception and interpretating the biofeedback information, the demand of ubiquitous biosensing and display technologies, and field evaluation in order to understand the use of biofeedback in everyday environments. We expect that various emerging HCI technologies could be used to address these challenges. New interaction designs as well as biofeedback paradigms can be further explored in order to for improve the accessibility, usability, comfort, engagement with, and user experience of biofeedback in everyday use.